2013
DOI: 10.1371/journal.pone.0078219
|View full text |Cite
|
Sign up to set email alerts
|

On the Myths of Indicator Species: Issues and Further Consideration in the Use of Static Concepts for Ecological Applications

Abstract: The use of static indicator species, in which species are expected to have a similar sensitivity or tolerance to either natural or human-induced stressors, does not account for possible shifts in tolerance along natural environmental gradients and between biogeographic regions. Their indicative value may therefore be considered at least questionable. In this paper we demonstrate how species responses (i.e. abundance) to changes in sediment grain size and organic matter (OM) alter along a salinity gradient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 58 publications
1
46
0
6
Order By: Relevance
“…Further, SAIs differ from correlations in species richness or composition in that their values differ depending on which taxon is the target and which is the surrogate (that is, SAIs give two values for each pair of taxa, in contrast to correlations which give a single value for each pair). We found only six articles (and 104 observations) that used the SAI for assessing the degree of complementarity between taxa, possibly because there are many methods for assessing congruence in the complementarity literature 29 . Although six articles was too few to make broad comparisons regarding the influence of study design or location on observed levels of congruence, we were able to make some broad observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, SAIs differ from correlations in species richness or composition in that their values differ depending on which taxon is the target and which is the surrogate (that is, SAIs give two values for each pair of taxa, in contrast to correlations which give a single value for each pair). We found only six articles (and 104 observations) that used the SAI for assessing the degree of complementarity between taxa, possibly because there are many methods for assessing congruence in the complementarity literature 29 . Although six articles was too few to make broad comparisons regarding the influence of study design or location on observed levels of congruence, we were able to make some broad observations.…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved either by comparing species composition between taxa using Mantel tests 23,24 or by calculating the degree of overlap between optimal subsets of sites for each taxon 25,26 (an approach based on the principle of complementarity 27 ). Although these developments have been valuable, they present a challenge to those attempting to synthesize global knowledge on cross-taxon congruence because of the array of different methods that have been applied in the literature 28,29 . Therefore, despite the publication of a number of valuable reviews of the congruence literature 15,28,[30][31][32][33][34] , one important theme has yet to be addressed; namely, the observation that congruence is often highly variable when measured in different locations or at different times 29,35,36 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a given species was included in a single ecological group) (Borja et al, 2000(Borja et al, , 2011. Others suggested that it is possible to observe different responses of species to organic matter, stress and pollution according to local and regional particularities (GrĂ©mare et al, 2009;Zettler et al, 2013). This could correspond to the existence of distinct adapted populations that can respond differently to pollution and, therefore, and be classified in several ecological groups in function to their sensitivity (GrĂ©mare et al, 2009;Zettler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Marine Science | www.frontiersin.orgclassification database as opposed to a more widely used one (e.g., the AMBI classification database) was driven by findings that species can shift their tolerances between biogeographic regions with different dominant environmental gradients (Zettler et al, 2013) and the need to adjust species classification to ecological groups identified for the Aegean by Simboura and Reizopoulou (2007) and Çinar et al (2012).…”
Section: Benthic Datamentioning
confidence: 99%